Student nurses' perceptions of reflective journal writing: A poststructuralist approach - Chick, Lorraine (University of Ottawa (Canada), 2004)
Within the profession of nursing, reflective journal writing is enthusiastically endorsed as an essential pedagogical strategy for producing reflective practitioners. Despite a lack of empirical evidence to substantiate the claims associated with reflective journaling, the prevailing belief in contemporary nursing education reflects an assumption that this practice is essential in the production of critically engaged nurses. This has resulted in a totalizing discourse that presents the adoption of reflective journaling within nursing curricula as unproblematic. This study combines the methodological principles of grounded theory, along with a poststructuralist approach, to explore the experience of reflective journaling from the perspective of university nursing students. Application of a Foucauldian analysis demonstrates how assumptions related to the utility of reflective journal writing are embedded within a variety of powerful discourses that shape how we think and speak about this practice. Of particular relevance is Foucault's exploration of the impact of surveillance, observation and disciplinary power. Reflective journaling is identified as a ritual of confession that produces self-regulating and compliant students. This study reveals that journal writing is largely viewed as a prescribed activity and assumptions are made by nurse educators regarding the ability of journals to facilitate critical reflection. The discourses that emerged from this analysis reflect different aspects of the socialization process that ultimately results in the construction of an "authentic" nurse. In closing, students and nurse educators are encouraged to develop alternative discourses that challenge the uncritical acceptance of reflective journal writing within contemporary nursing education.
Keywords: Health Sciences, Education.; Health Sciences, Nursing.; Education, Higher.